Direct arylation polymerization toward a D-A type copolymer based on carbazole and benzothiadiazole units - An analogue of PCDTBT - Mohd Sani Sarjadi; Wong, Xin Lin; Farah Hannan Anuar; Zuhair Jamain; Md. Lutfor Rahman (Malaysian Institute of Chemistry, 2020)
Poly[N-9’-heptadecanyl-2,7-carbazole-alt-5,5-(4’,7’-di-2-thienyl-2’,1’,3’-benzothiadiazole)] (PCDTBT) is an attractive material for optoelectronic devices, and has been prevalently prepared by traditional couplings. Despite robust and effective, the traditional methods generally involve the use of toxic organometallic reagents. Direct arylation polymerization (DArP), as a simple, green, and cost-effective alternative to traditional coupling, has been utilized in this work to prepare an analogue of PCDTBT, namely poly[(9-hexadecyl-2,7-carbazole)-alt-(4,7-di(thiophen-2-yl)-2,1,3-benzothiadiazole)] (P1). The co-polymer was obtained in 44% yield and satisfactorily characterized by Fourier-transform infrared spectroscopy (FTIR)and Nuclear magnetic resonance (NMR). UV-Vis absorption spectra showed the presence of inter-chain interaction and aggregation in the solid state. The optical band gap of the co-polymer was found to be in the range of 1.77 -1.81 eV, which is slightly lower than that of PCDTBT (1.88 eV).